Simultaneous L4-5 Transforaminal and L5-S1 Interlaminar Percutaneous Endoscopic Lumbar Discectomy for L4-5 Down Migrated Disc: A Technical Case Report - Sang Soo Eun; Sang-Ho Lee (Journal of Minimally Invasive Spine Surgery and Technique, 2016)
A 44 years-old woman was diagnosed as L4-5 down migrated disc herniation and decided for percutaneous endoscopic lumbar discectomy (PELD). Since significant amount of disc material is present in both subannular lesion and down migrated portion, transforaminal approach for L4-5 and interlaminar approach for L5-S1 were planned. Herniated disc was successfully removed. Simultaneous transforaminal and interlaminar PELD can be an minimal invasive option for treatment of migrated disc herniation in selected cases.